Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to formally prove, by Cauchy definition of limit, that $\lim\limits_{x\rightarrow 0^{+}}\frac{f(x)}{g(x)}=1$ implies that also $\lim\limits_{x\rightarrow 0^{+}}\frac{f^{-1}(x)}{g^{-1}(x)}=1$, where $f^{-1}$ (or $g^{-1}$) denotes the inverse function of $f$ (or $g$), functions $f$ and $g$ are both continuous and strictly increasing and $f(0)=g(0)=0$?

share|cite|improve this question

Unless I am mistaken, the result does not hold. Here is a counterexample.

Define $f$ and $g$ on $I=[0,\mathrm e^{-1})$ by $f(0)=g(0)=0$ and, for every positive $x$ in $I$, $$ \frac1{f(x)}=\log\left(\frac1x\right)-\log\log\left(\frac1x\right),\qquad\frac1{g(x)}=\log\left(\frac1x\right). $$ Then $f$ and $g$ are continuous and increasing on $I$. Furthermore, $\log(u)\ll u$ when $u\to+\infty$, hence $\log\log\left(\frac1x\right)\ll\log\left(\frac1x\right)$ when $x\to0^+$, which implies that $$ \lim\limits_{x\to0^+}\frac{f(x)}{g(x)}=1. $$ The inverse functions $f^{-1}$ and $g^{-1}$ are defined on $J=[0,1)$ and $g^{-1}(y)=\mathrm e^{-1/y}$ for every $y$ in $J$. Writing $f^{-1}(y)$ as $$ f^{-1}(y)=\mathrm e^{-1/y}\cdot y\cdot (1+z(y)), $$ one gets after some easy algebra that $z(y)$ solves the equation $$ z=y\cdot(\log(1+z)-\log(y)). $$ From there, one sees that $z(y)\to0$ when $y\to0^+$ hence $$ \lim\limits_{y\to0^+}\ \frac{f^{-1}(y)}{g^{-1}(y)}=\lim\limits_{y\to0^+}\ y\cdot(1+z(y))=0. $$

share|cite|improve this answer
Ok, I followed by your suggestions and I'm able to prove that $f^{-1}(vy)\leq g^{-1}(y)\leq f^{-1}(uy)$ for y from some neighborhood of 0 but I really can't see in what exactly way I should use the continuity assumption to get desired result. Could you explain me it in more detailed way? Thank you. – Mark Nov 7 '11 at 13:40
My so-called hint led to a dead end, sorry about that. See the revised version. – Did Nov 7 '11 at 17:36
Good example (+1). For me, a slightly easier way to see what is going on here is to notice that $$\exp(-1/f(x)) = -x\log(x)$$ and $$\exp(-1/g(y)) = y$$ So if $f(x)=g(y)$, then $y=-x\log(x)$. Thus, $y/x=-\log(x)\to\infty$. – robjohn Nov 7 '11 at 21:25
In fact, it seems that $$\frac{g^{-1}(z)}{f^{-1}(z)}=-\log(f^{-1}(z))$$ – robjohn Nov 7 '11 at 21:35

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.